Integrated transcriptome and hormone analyses provide insights into silver thiosulfate-induced “maleness” responses in the floral sex differentiation of pumpkin (Cucurbita moschata D.) - Li, Qingfei; Chen, Peiwen; Tang, Hao; Zeng, Fansen; Li, Xinzheng (Frontiers in Genetics, 2022)
The perfect mating of male and female flowers is the key to successful pollination. The regulation of ethylene with chemicals is a good option for inducing staminate or female flowers. Silver thiosulfate is often used to induce the formation of male flowers in subgynoecious and gynoecious crops, which is important to maintain their progenies. However, its effects on flower sex differentiation in pumpkin (Cucurbita moschata Duch.) and the underlying mechanism remain unclear. In this study, the application of silver thiosulfate to pumpkin seedlings significantly delayed the occurrence of the first female flower and increased the number of male flowers. We next investigated the underlying mechanism by employing transcriptome and endogenous hormone analyses of the treated plants. In total, 1,304 annotated differentially expressed genes (DEGs)were identified by comparing silver thiosulfate-treated and control plants. Among these genes, 835 were upregulated and 469 were downregulated. The DEGs were mainly enriched in the phenylpropanoid biosynthesis and metabolism pathways (phenylalanine ammonia-lyase, peroxidase) and plant hormone signal transduction pathways (auxin signaling, indole-3-acetic acid-amido synthetase, ethylene response factor). Silver thiosulfate significantly reduced the levels of 2-oxindole-3-acetic acid, para-topolin riboside, dihydrozeatin-O-glucoside riboside, and jasmonoyl-l-isoleucine but increased the levels of trans-zeatin-O-glucoside, cis-zeatin riboside, and salicylic acid 2-O-β-glucoside. The levels of auxin and jasmonic acid were decreased, whereas those of salicylic acid were increased. Different trends were observed for different types of cytokinins. We concluded that silver thiosulfate treatment not only affects the expression of auxin synthesis and signaling genes but also that of ethylene response factor genes and regulates the levels of auxin, salicylic acid, jasmonic acid, and cytokinins, which together might contribute to the maleness of pumpkin. This study provides useful information for understanding the mechanism underlying the effect of silver thiosulfate on floral sex differentiation in pumpkin, a widely cultivated vegetable crop worldwide, and gives a production guidance for the induction of maleness using STS for the reproduction of gynoecious lines of Cucurbitaceae crops.